The buried bumper syndrome: migration of internal bumper of percutaneous endoscopic gastrostomy tube into the abdominal wall - (:unkn) unknown (SPRINGER-VERLAG TOKYO, 2003)
A percutaneous endoscopic gastrostomy tube was inserted in a 59-year-old man who was undergoing craniotomy due to subarachnoid hemorrhage, because it was estimated that he could not have oral intake for a period of 4 weeks. Seventy days after the insertion, the percutaneous endoscopic gastrostomy tube was replaced because of its accidental removal by the patient. Two months after the second insertion, the tube had to be replaced due to nonfunctioning. The buried bumper syndrome was diagnosed on physical examination, and was confirmed by endoscopy, with findings of mucosal dimpling and nonvisualization of the internal bumper. The tube was removed by external traction without any abdominal incision, and the same site was used for the insertion of a replacement tube over a guidewire. The patient remained symptom-free during 18 months of follow-up.
Keywords: percutaneous endoscopic gastrostomy; buried bumper syndrome; FOLLOW-UP; COMPLICATION; PEG